2014
DOI: 10.1002/jtr.2007
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Social Responsibility Strategy in the Hotel Industry: Evidence from the Balearic Islands

Abstract: This paper attempts to identify some of the main factors affecting a hotel establishment's decision to adopt (or not), and to what extent, socially and environmentally responsible business practices. Salient among the results obtained is the fact that corporate social responsibility (CSR) is likely to be part of a hotel's product differentiation strategy; additionally, it is shown that productivity aspects such as scale economies, as well as the hotel's internal organization, also impact a hotel's CSR strategy. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
1
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 34 publications
0
23
1
4
Order By: Relevance
“…This solution confirms H3, which we defined as "hotel groups with brands in the luxury segment will involve customers more in their philanthropic activities and this will make the group more disposed to undertake corporate philanthropy." The different solutions obtained in this analysis do not enable us to infer what other authors conclude about luxury hotels being more involved in their communities (Calveras, 2015;Stylos & Vassiliadis, 2015). On the contrary, our solutions revealed participation for both below-luxury and luxury hotels.…”
Section: Why Hotel Groups Get Involved In Their Communitiescontrasting
confidence: 91%
See 3 more Smart Citations
“…This solution confirms H3, which we defined as "hotel groups with brands in the luxury segment will involve customers more in their philanthropic activities and this will make the group more disposed to undertake corporate philanthropy." The different solutions obtained in this analysis do not enable us to infer what other authors conclude about luxury hotels being more involved in their communities (Calveras, 2015;Stylos & Vassiliadis, 2015). On the contrary, our solutions revealed participation for both below-luxury and luxury hotels.…”
Section: Why Hotel Groups Get Involved In Their Communitiescontrasting
confidence: 91%
“…Out of the 35 papers found in the literature review, only nine papers included any reference to luxury segments, and only three of these papers included results focused on that segment (Calveras, 2015;Li et al, 2015;Stylos & Vassiliadis, 2015). Other papers made some reference to donations by luxury hotels (C. A.…”
Section: Hypothesesmentioning
confidence: 99%
See 2 more Smart Citations
“…Previously presented studies primarily recognised the importance of CSR in large manufacturing enterprises and within the hotel (lodging) sector. To date, research findings into CSR in hotel industry have confirmed that if hotel organizations adopt and integrate CSR into their organizational strategies, they can facilitate innovativeness (Čivre and Gomezelj Omerzel 2015;Calveras 2015); increase and/or improve their organizational competitiveness (Kang et al 2015;Garay and Font 2012) and brand image (Tingchi et al 2014); boost employees' and customers' loyalty (García de Leaniz and Rodríguez Del Bosque Rodríguez 2015; Lee 2016); conserve environments (Rahman and Post, 2012), while at the same time contributing to solving problems in society that may arise (Smith and Ong 2015). According to Chen (2015) travellers are progressively more concerned with how tourist companies make their money and are expecting businesses to engage in responsible activities.…”
Section: Literature Reviewmentioning
confidence: 98%